Think twice : harnessing the power of counterintuition - Mauboussin, Michael J., 1964- (Harvard Business Press, 2009)
Leaders in business, medicine, law and government make crucial decisions every day. The harsh truth is that they mismanage many of those choices, even though they have the right intentions. Why is it so hard to make sound decisions? Mauboussin offers powerful rules for avoiding error.